Japanese health and safety information for overseas visitors: a randomized controlled trial - Mariko Nishikawa; Masaaki Yamanaka; Akira Shibanuma; Junko Kiriya; Masamine Jimba (BMC, 2023)
Abstract Introduction International travel to Japan increased steadily until the coronavirus disease 2019 (COVID-19) outbreak. Although international travel was curtailed worldwide due to the pandemic, the number of overseas visitors to Japan should increase again after the restrictions are lifted. We assessed the effect of a five-minute digital game on the knowledge of health information and the level of satisfaction with educational health resources of overseas visitors to Japan. Methods We conducted a randomized controlled trial among 1062 previous and potential visitors to Japan utilizing an internet portal. We recruited previous and potential visitors to Japan from the internet portal sites of the UK, the US and Australia. We randomly allocated participants to two groups: an intervention group that played an animated game and a control group that viewed an online animation. All participants answered a self-administered questionnaire online from March 16 to 19, 2021. We assessed visitors' levels of health knowledge and satisfaction using the CSQ-8. We analyzed the data with a t test and the difference in differences test. Our RCT followed the SPIRIT guidelines. Results Of the 1062 previous and potential visitors recruited via the three countries' internet portals (354 from each country), some had visited Japan previously (174 in the intervention group, 220 in the control group), while some were potential visitors to Japan (357 in the intervention group, 311 in the control group). Some had gathered health and safety information about Japan prior to this study (180 in the intervention group, 211 in the control group). Both groups improved their health information levels after the intervention. The level of satisfaction with health information in Japan was significantly increased in the intervention group (average difference of 4.5 points) compared to that in the control group (average difference of 3.9 points) (p < 0.05). Both groups' mean CSQ-8 scores increased significantly after the intervention (p < 0.001): from 23 to 28 in the intervention group and from 23 to 24 in the control group. Conclusions Our study introduced unique educational strategies using an online game to provide health and safety information to previous and potential visitors to Japan. The online game was a more effective way to increase satisfaction than the online animation about health information. This study was registered in the UMIN-CTR (University Hospital Medical Information Network Center Clinical Trials Registry) as Version 1, and the trial registration data are available as UMIN000042483, 17/11/2020. Trial registration Trials UMIN-CTR (University Hospital Medical Information Network Center Clinical Trials Registry), UMIN000042483 (Japanese health and safety information for overseas visitors: A randomized controlled trial), 17/11/2020.